Mathematics Learning for Deaf Students: A Case Study in an Inclusive Classroom - Amiyani, Rofi; Adhiwibowo, Bayu (Prodi Tadris Matematika Fakultas Tadris Umum, 2025)
Deaf students face significant challenges in learning mathematics, a subject heavily reliant on verbal communication and abstract concepts. Inclusive education aims to create an environment that supports all students, including those with physical and cognitive differences. The current study, therefore, sets out to gain a deeper understanding of how mathematics for deaf learners is enacted within an inclusive classroom setting, including how the mathematics curriculum is adapted to serve the needs of deaf learners in response to translation and cognitive access challenges. The study was conducted in Class 12B at Tumbuh Senior High School, Yogyakarta, in the 2023-2024 academic year. This study uses a qualitative descriptive approach and is framed as a case study. The class includes eight students: five are typical learners, one has an anxiety disorder, and two are deaf. Over a year, data were gathered through classroom observations, in-depth interviews with the support teacher, interviews with students from Class 12B, and discussions with other math teachers to gain broader insight into teaching approaches across classrooms. The findings show that teaching in Class 12B is rooted in inclusive values. Teachers are able to customize lessons to the individual needs of each student. Instead of a one-size-fits-all approach, the teacher differentiates learning by varying the depth of the content, selecting relatable examples, providing different exercises, and adjusting assessments. These efforts support students with unique learning and special needs to continue participating in the learning process.